Primary prevention programme for burnout-endangered teachers: follow-up effectiveness of a combined group and individual intervention of AFA breathing therapy - Götz, Katja; Loew, Thomas; Hornung, Regina; Cojocaru, Laura; Lahmann, Claas; Tritt, Karin (Evidence-based complementary and alternative medicine, 2013)
Background. Early retirement of teachers due to burnout is frequent in Germany. In this study short- and medium-term effects of AFA breathing therapy were evaluated. Methods. This study was designed as a longitudinal controlled intervention design with four points of measurements: before assessment (T1), after intervention (T2), three months (follow up 1) (T3) after intervention, and six months (follow up 2) after intervention (T4). The intervention lasted a total of 11 weeks (weekly group therapy for eight weeks and three weeks of individual breathing session). The effects of intervention were measured with the questionnaire “work-related behaviour and experience Patterns” (AVEM) at four times. Results. In the intervention group 64 teachers and in the self-selected control group 27 teachers were included. The AVEM scales “subjective significance of work” and “professional ambition” changed over time and within both groups (interaction effect). Significant improvements over the four measurements were observed in the intervention group in two AVEM scales: “emotional distancing” ( ; ) and “balance and mental stability” ( ; ). Conclusions. AFA breathing therapy showed short- and medium-term effects in the intervention group over four points of measurements. It may be assumed that breath therapy supports teachers in resisting occupational demand.
Gesehen am 11.02.2020